Analisis Strategi Relationship Marketing Pada Dimensi Social Benefit Pt. Bank Pembiayaan Rakyat Syariah (BPRS) Berkah Dana Fadhlillah Kabupaten Kampar - Yusriadi, Yusriadi (Eko dan Bisnis: Riau Economic and Business Review, 2023)
This research aims to analyze Relationship Marketing Strategy in the Social Benefit dimension of PT. Sharia People's Financing Bank (BPRS) Berkah Dana Fadhlillah Kampar Regency. With a total of 140 respondents, through descriptive analysis the results of the application of relationship marketing strategies in the social benefit dimension were high with an average score of 4.31 with the highest score being 4.46 with the statement "employees show a friendly attitude, smile and say their name." when serving customersâ€ and the lowest with a score of 3.95 with the statement â€œemployees serve customers well